Optimal Pricing and Quality of Academic Journals and the Ambiguous Welfare Effects of Forced Open Access: A Two-Sided Model - Frank Mueller-Langer; Richard Watt (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2013)
We analyse optimal pricing and quality of a monopolistic journal and the optimality of open access in a two-sided model. The predominant aspect of the model that determines the quality levels at which open access is optimal is the nature of the (non-linear) externalities between readers and authors in a journal. We show that there exist scenarios in which open access is a feature of highquality journals. Besides, we find that the removal of copyright (and thus forced open access) will likely increase both readership and authorship, will decrease journal profits, and may increase social welfare.
Keywords: L11; L82; O34; 330; two-sided markets; academic journals; open access; removal of copyright; welfare effects